The politics of global supply chains power and governance beyond the state - Macdonald, Kate 1976- (Polity Press, 2014)
This is the first book to deal with 'supply chain politics' a phrase that is becoming increasingly commonplace. The book focuses primarily on coffee and garment supply chains, using these as case studies, showing how the political struggles within them both reflect and fuel the on-going re-shaping of global governance.